Description of the Pediasuit ProtocolTM - Eduardo Mendonça Scheeren; Luis Paulo Gomes Mascarenhas; Claudiana Renata Chiarello; Ana Cláudia Martins Szczypior Costin; Leonardo Oliveira; Eduardo Borba Neves
INTRODUCTION: PediaSuit ProtocolTM is an intensive therapy with a holistic approach to the treatment of individuals with neurological disorders like cerebral palsy (CP), developmental delays, traumatic brain injuries, autism and other conditions which affect a child's motor and/or cognitive functions. OBJECTIVE: The aim of the present work is to describe the PediaSuit ProtocolTM. METHODS: The authors team remained two months observing the care provided in a clinic with physical therapists trained by the PediaSuit ProtocolTM team (USA). RESULTS: The PediaSuitTM is a therapeutic protocol which uses a suit combined with intensive physical therapy and consists of up to four hours of therapy a day, five days a week, during three or four weeks. The PediaSuit ProtocolTM is customized to fit the needs of each child, with specific functional goals, and usually involves an intensive rehabilitation program. It combines the best elements of various techniques and methods, and has a sound rationale based on exercise physiology. CONCLUSION: This protocol anticipates results obtained only with long periods of conventional physical therapy.